Romeo & Juliet [Rómeo a Júlia anglicky] - Shakespeare, William, 1564-1616 (Sweet Cherry Publishing : [distributor] Sweet Cherry Publishing, 2020)
Hailed as one of the greatest romantic tragedies ever written, William Shakespeare´s Romeo and Juliet is the tragic love story of the star-crossed lovers, Romeo and Juliet. Set in the city of Verona, italy, the play revolves around the feud between two affluent families, the Montagues and the Capulets. Despite the enmity, Romeo Montague and Juliet Capulet fall passionately in love and wed in secret. However, the curse of enmity overpowers and everything goes terribly wrong.